Removal of ammonia from aqueous solutions by ligand exchange onto a Cu(ii)-loaded chelating resin: kinetics, equilibrium and thermodynamics. Issue 21 (23rd February 2017) - Chen, Quanzhou; Zhou, Kanggen; Chen, Yan; Wang, Aihe; Liu, Fang
Abstract : A poly ligand exchanger (PLE), Cu(ii )-loaded chelating resin (ammonia adsorption reagent, named AMAR) was prepared to efficiently remove ammonia from solutions by ligand exchange. Abstract : A poly ligand exchanger (PLE), Cu(ii )-loaded chelating resin (ammonia adsorption reagent, named AMAR) was prepared to efficiently remove ammonia from solutions by ligand exchange. The kinetics, equilibrium and thermodynamics of the ligand sorption of ammonia onto AMAR from the synthesized solution were investigated under different experimental conditions. AMAR was characterized using FT-IR and a Micromeritics ASAP2020 surface area and porosity analyzer. The FT-IR analysis and pore textural property studies verified the functional group of weak iminodiacetate acid and reveal the combination form of Cu(ii ) with AMAR. The batch experiments with respect to different solution pHs, temperatures, initial ammonia concentrations and contact times were investigated. The equilibrium sorption experiments suggested that the optimum pH for ammonia adsorption was 9.5. The ammonia adsorption capacity on AMAR increased with the increase of contact time and initial ammonia concentration and decreased with the increase of temperature. The Langmuir ( R 2 > 0.99) isotherm model was the best fitted model compared with the Freundlich model ( R 2 > 0.91). The kinetic data were fitted well with the pseudo-second-order model compared with the pseudo-first-order and intra-particle models. The kinetic data confirmed that particle diffusion is not the only rate-limiting step in the adsorption process. The adsorption process might be affected by a variety of mechanisms. The maximum adsorption capacity was 42.735 mg g −1, indicating that AMAR was a promising and efficient ammonia adsorption reagent.